(untitled) (Docentes 2.0 Journal, 2025)
Social media has become essential to everyday life in recent decades, especially among teenagers. Digital platforms such as Facebook, Instagram, Twitter, and WhatsApp are fundamental spaces for interaction and expression today. The research aimed to analyze how the intensive use of digital platforms affects high school students’ writing skills and comprehension. The research was based on the systematic method, phenomenological paradigm, hermeneutic, and qualitative approach, with a narrative-descriptive design of a bibliographic documentary type and cross-sectional. The sample of this research included high school students from various provinces. The methodology used included bibliographic reviews, the analysis of different academic databases, and surveys and observations to obtain a comprehensive view of the use of digital language among teenagers. The results indicated that the language used on social media, characterized by textisms, omission of accents, and lack of punctuation, contributes to the deterioration of young people’s spelling skills. It is also observed that these errors are transferred to the academic field. It was also identified that instant communication, together with geography, reflects a trend toward the simplification of linguistic norms. Although the use of social networks facilitates communication and entertainment, it poses significant challenges in developing formal linguistic competencies. Implementing educational methodologies that motivate students to distinguish between informal and academic registers is recommended, as well as encouraging appropriate use of language in various contexts.